Contextual Teaching Learning Inovasi dalam Strategi Pembelajaran di Bidang Pendidikan Akuntansi - Christine Dwi; Lidya Agustina (Universitas Kristen Maranatha, 2007)
The aims of educational strategy is to help students see meaning in the academic material they are studying by connecting academic subject with the context of their dailylives. Contextual teaching & learning is one of the learning strategies, that is a new strategy who help help students see meaning in the academic material they are studyingby connecting academic subject with the context of their daily lives, and the lecturers being the facilitator. For the future contextual teaching & learning is expected to renewal accounting educational system in Indonesia. To achieve contextual teaching & learning aims the system and composes the following eight components : making meaningfull conections, doing significant work, selfregulated learning, colaborating, critical and creative thinking, nurturing the individual, reaching high standards, using autentic assessment. Another component to completed the learning strategy, need Emotional Quotient (EQ) of the student self, because of that student will be motivated and meaning academic material.Keywords : learning strategy, contextual teaching & teaming, emotional Quotient.